2009
DOI: 10.1007/s11051-009-9698-7
|View full text |Cite
|
Sign up to set email alerts
|

Trends for nanotechnology development in China, Russia, and India

Abstract: China, Russia, and India are playing an increasingly important role in global nanotechnology research and development (R&D). This paper comparatively inspects the paper and patent publications by these three countries in the Thomson Science Citation Index Expanded (SCI) database and United States Patent and Trademark Office (USPTO) database (1976–2007). Bibliographic, content map, and citation network analyses are used to evaluate country productivity, dominant research topics, and knowledge diffusion patterns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(26 citation statements)
references
References 27 publications
0
26
0
Order By: Relevance
“…Focusing on the specific area of nano field, Larsen (2008) examined the knowledge structure in the field of nanostructured solar cell research by analyzing coauthorship network of countries/regions and cocitation network of journals. Liu et al (2009) analyzed the citation network of papers at institution level and compared the structure and knowledge diffusion patterns in nano field in China, Russia, and India. In addition, Liu et al (2014) used coauthorship network of researchers in nano field to investigate the structure and impact of research networking.…”
Section: Nanoscience and Nanotechnology Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…Focusing on the specific area of nano field, Larsen (2008) examined the knowledge structure in the field of nanostructured solar cell research by analyzing coauthorship network of countries/regions and cocitation network of journals. Liu et al (2009) analyzed the citation network of papers at institution level and compared the structure and knowledge diffusion patterns in nano field in China, Russia, and India. In addition, Liu et al (2014) used coauthorship network of researchers in nano field to investigate the structure and impact of research networking.…”
Section: Nanoscience and Nanotechnology Networkmentioning
confidence: 99%
“…Various forms of network were derived in prior studies depending on the choice of analysis elements and relationship indicators. Specifically, the nodes were defined using various academic units, including patent documents (Li et al 2007;Chang et al 2010), paper documents (Rafols and Meyer 2010;Takeda et al 2009), journals (Leydesdorff and Zhou 2007;Leydesdorff 2007a, b;Larsen 2008), authors (Liu et al 2014;Rueda et al 2007), technology fields (Huang et al 2004;Li et al 2007), science fields (Porter and Youtie 2009; Rafols and Meyer 2010), institutions (Huang et al 2004;Li et al 2007;Liu et al 2009), and countries/regions (Huang et al 2004;Li et al 2007;Larsen 2008;Zheng et al 2014;Dang et al 2010). The links among academic units were specified using common measures of bibliometrics, which are citation (Huang et al 2004;Leydesdorff and Zhou 2007;Leydesdorff 2007a, b;Porter and Youtie 2009;Li et al 2007;Liu et al 2009), intercitation (Takeda et al 2009), cocitation (Larsen 2008), bibliographic coupling (Rafols and Meyer 2010), and coauthorship (Larsen 2008;Liu et al 2014;Rueda et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Early research has suggested that nanotechnology is a general purpose technology with broad applicability throughout the economy [21].Various studies have shown that nanotechnology continues to demonstrate an overall upward trend in publication and patent activity [22][23][24][25][26][27] and its subfields [28][29][30] or in a specific country or region [31][32][33][34], the multidisciplinarity and interdisciplinarity of nanotechnology [35][36][37][38] , visualization of nanotechnology at discipline level [39] and the collaboration level [36,38], analysis at the individual level [40][41][42], and other topics [43][44][45].…”
Section: Methodsmentioning
confidence: 99%
“…Egypt produced 5236 publications over the same period -placing this country in a leading position in N&N on the African continent. Chen et al 28 found that Russia, India and China showed rapid growth in N&N publications from 2000 to 2007 of about 12.8 times in China, 8 times in India and 1.6 times in Russia. What is apparent is that N&N is growing very rapidly while the growth in South Africa has been recorded to be below that of other countries.…”
Section: The Nanotechnology Publication Trend In South Africamentioning
confidence: 99%